Synchronous thyroid paraganglioma and urachal adenocarcinoma, an unusual diagnosis - Toribio Ruano, Ignacio (2021)
Paragangliomas (PG) are uncommon head and neck tumors and their location in the thyroid gland is even more exceptional. Likewise, urachal adenocarcinomas are unusual and poorly studied neoplasms. We report the case of a patient where a left thyroid nodule was found in the course of an extended radiological study due to a urachal adenocarcinoma. Two inconclusive fine-needle aspirations (FNA) were performed, and in light of the oncological history, a diagnostic hemithyroidectomy was elected. The histological diagnosis was thyroid paraganglioma. The patient deceased as a consequence of lung metastasis from the urachal adenocarcinoma, so the following studies could not be fulfilled. This is de first reported case of synchronous thyroid PG and urachal adenocarcinoma and the seventh of PG in a male patient.